2011
DOI: 10.1091/mbc.e11-04-0364
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP18, a GTPase-activating protein for RhoA, controls cell shape, spreading, and motility

Abstract: Using a library of siRNAs, we found that ARHGAP18 was essential for the organization of actin stress fibers and focal adhesion. ARHGAP18 is one of the crucial factors for the regulation of RhoA in order to control cell motility and spreading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 46 publications
6
97
0
Order By: Relevance
“…Maeda et al previously reported that silencing of ARHGAP18 in epithelial cell lines induces a contracted phenotype with reduced spreading and pronounced stress fibers and focal adhesions. 26 Silencing of ARHGAP18 with the different siRNAs in EC did not result in gross morphological changes with the exception of siRNA-2, where significant cell elongation (Fig. S1B) was observed.…”
Section: Knockdown Of Arhgap18 Promotes Ec Migration and Sproutingmentioning
confidence: 83%
See 3 more Smart Citations
“…Maeda et al previously reported that silencing of ARHGAP18 in epithelial cell lines induces a contracted phenotype with reduced spreading and pronounced stress fibers and focal adhesions. 26 Silencing of ARHGAP18 with the different siRNAs in EC did not result in gross morphological changes with the exception of siRNA-2, where significant cell elongation (Fig. S1B) was observed.…”
Section: Knockdown Of Arhgap18 Promotes Ec Migration and Sproutingmentioning
confidence: 83%
“…Interestingly ARHGAP18 displays RhoA and Rho1 (Drosophila RhoA homolog) GAP activity in epithelial cell lines and Drosophila S2 cells, respectively. 26,35 Such epithelial-endothelial differences in RhoGAP specificity have also been demonstrated in other RhoGAP family members, such as ARHGAP24/VasGAP/FliGAP. [36][37][38] RhoC belongs to the Rho subfamily and shares 92% sequence similarity but is functionally distinct as RhoC promotes, whereas RhoA inhibits tumor cell invasion and migration.…”
Section: E975002-8mentioning
confidence: 85%
See 2 more Smart Citations
“…For instance, CTDSP1, an inversely correlated potential miR-183 target, has been shown to be involved in silencing neuronal genes through interaction with REST/NRSF, and CTDSP1 inactivation was found to promote neuronal differentiation of P19 stem cells (Yeo et al 2005). On the other hand, knockdown of ARHGAP18, a potential miR-183 target, enhanced stress fiber formation and induced rounding of cells (Maeda et al 2011). Likewise, potential miR-96 target genes included FARP1 that has been shown to promote dendritic growth of spinal motor neurons subtypes (Zhuang et al 2009) and LGI1 that has been implicated in the formation, differentiation, maintenance, and plasticity of neuronal synapses (Ko & Kim 2007).…”
Section: Mir183/96 Contribute To Pcc/pgl Tumorigenesis By Interferingmentioning
confidence: 99%